2023
DOI: 10.1111/odi.14533
|View full text |Cite
|
Sign up to set email alerts
|

PDZ‐binding kinase inhibitor OTS514 suppresses the proliferation of oral squamous carcinoma cells

Abstract: ObjectivePDZ‐binding kinase (PBK) has been reported as a poor prognostic factor and is a promising molecular target for anticancer therapeutics. Here, we aimed to investigate the effect of specific PBK inhibitor OTS514 on the survival of OSCC cells.MethodsFour OSCC cell lines (HSC‐2, HSC‐3, SAS, and OSC‐19) were used to examine the effect of OTS514 on cell survival and apoptosis. DNA microarray analysis was conducted to investigate the effect of OTS514 on gene expression in OSCC cells. Gene set enrichment anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Through consulting the literature , we were particularly interested in PBK, which is overexpressed in several human malignancies 20–24 . By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through consulting the literature , we were particularly interested in PBK, which is overexpressed in several human malignancies 20–24 . By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5.…”
Section: Resultsmentioning
confidence: 99%
“…Through consulting the literature, we were particularly interested in PBK, which is overexpressed in several human malignancies. [20][21][22][23][24] By analyzing the amino acid sequence of PBK, we found that PBK at Thr9 may be the potential phosphorylation site of CDK5. To further verify that CDK5 phosphorylates PBK-T9, HEK293 cells were transfected with GFP-CDK5 and FLAG-PBK.…”
Section: Phosphorylation Of Pbk At Thr9 By Cdk5 Promotes Cell Prolife...mentioning
confidence: 99%